Implicit Religion and the Meaning Making Model - Park, Crystal L. (Implicit religion, 2011)
This article explores the potential contributions of a model of meaning making (Park 2010a) to the emerging study of implicit religion. A model of meaning making is first explicated; this model describes the ways in which meaning is central to human beings in both their everyday lives and in stressful circumstances and delineates global and situational levels of meaning. Previous applications of the meaning making model to religiousness/spirituality are discussed. The concept of implicit religion is introduced, and implications of its integration into a broader religious meaning-making model are considered. Suggestions for future research on implicit religion and meaning-making conclude the article.